Prescription of antibiotics in community-acquired pneumonia in children: are we following the recommendations? - Fonseca Lima EJ; Lima DEP; Serra GHC; Abreu e Lima MAZS; Mello MJG (Therapeutics and Clinical Risk Management, 2016)
Eduardo Jorge da Fonseca Lima,1,2 Débora Ellen Pessoa Lima,3 George Henrique Cordeiro Serra,2 Maria Anaide Zacche S Abreu e Lima,2 Maria Júlia Gonçalves de Mello1,2 1Instituto de Medicina Integral Professor Fernando Figueira – IMIP, Recife, PE, Brazil; 2Faculdade Pernambucana de Saúde – FPS, Recife, PE, Brazil; 3Universidade de Pernambuco, Recife, PE, Brazil Objective: To assess the adequacy of antibiotic prescription in children hospitalized for pneumonia in a reference pediatric hospital in Brazil. Methods: This was a cross-sectional study involving children aged between 1 month and 5 years who were hospitalized between October 2010 and September 2013. The classification of community-acquired pneumonia (CAP) was based on the clinical and radiological criteria of the World Health Organization (WHO). The analysis of antibiotic adequacy was performed according to the main guidelines on CAP treatment, which include the WHO guidelines, Brazilian Society of Pediatrics guidelines, and international guidelines (Pediatrics Infectious Diseases Society, the Infectious Disease Society of America, British Thoracic Society, and Consenso de la Sociedad latinoamericana de Infectología). A multivariate analysis was performed including variables that have statistical significance of P≤0.25 in the bivariate analysis. Results: The majority of the 452 hospitalized children were classified as having severe or very severe CAP (85.18%), and inadequate empiric antimicrobial therapy was started in 26.10% (118/452) of them. Ampicillin was the most used empiric antibiotic therapy (62.17%) for pneumonia, followed by a combination of ampicillin and associated with gentamicin. The initially proposed regimen was modified in 29.6% of the patients, and the most frequent change was the replacement of ampicillin by oxacillin combined with chloramphenicol. The median hospitalization time was 8.5 days, and the lethality rate was 1.55%. There was no statistical difference in adequacy in relation to the severity of pneumonia or degree of malnutrition. In the bivariate analysis, inadequacy of antibiotic therapy regimen was higher in patients undergoing oxygen therapy (P<0.05), which was given to 219 patients (48.45%). Pleural effusion was observed in 118 patients (26.11%) and was associated with higher prescription inadequacy, and it was the only factor that remained in the multivariate analysis (odds ratio =8.89; 95% confidence interval 5.20–15.01). Conclusion: Adherence to the main guidelines for antimicrobial therapy according to the childhood CAP was unsatisfactory. Compliance with the guidelines is essential for both the management of pneumonia cases and the decrease in bacterial resistance and it is one of the cornerstone of WHO police of controlling antibiotic resistance. Keywords: antibiotic therapy, pneumonia, children, health services